Pengaruh Rekrutmen Dan Penempatan Terhadap Kinerja Karyawan Pada CV. Yen's Delight di Samarinda - Mudrikul Abror (Jurnal Administrasi Bisnis Fisipol Unmul, 2020)
Recruitment and placement is one of the keys to creating a professional Human Resources working in the company, as well as the selection of job placement places employee or prospective employee to make workers more efficient in carrying out their workload, and to enhance their skills and skills as a basis for running smooth tasks and assigns people rights and job titles to their interests and abilities. This study aimed to determine and analyze the impact of recruitment (X1) and placement (X2) on employee performance (Y) on CV. Yen's Delight in Samarinda. Primary data were obtained by interview 73 respondents using a questionnaire. Secondary data is obtained by conducting field observations. Data analysis using multiple regression techniques with a statistic software version of SPSS 22. The results show that the variables of recruitment consisting of basic hiring, recruitment resources, recruitment and placement consisting of education, work knowledge, experience, skills, quantity, quality, timeliness, attendance, supervisory cooperation ability influence employee performance. CV. Yen's Delight It is better to apply the recruitment method to further develop the recruitment method that has been applied to get more specific employee who are competent and apply good and correct placement methods so that the company pays more attention to the application of employee by follow their expertise and experience in their respective fields.